UPAYA MENINGKATKAN MOTIVASI DAN HASIL MELALUI COOPERATIVE SCRIPT MATERI KERJASAMA EKONOMI INTERNASIONAL SMAN 7 PONTIANAK - Hidayat, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to improve the learning process through cooperative script learning model to improve motivation and economic learning outcomes of students of class XI IIS 4 SMA Negeri 7 Pontianak. This study is a Classroom Action Research that collaborates with economic subject teachers conducted for two cycles. Data collection techniques used are tests and observations. Based on the results of research that has been done, that cooperative script learning model can improve the motivation and ability of student learning outcomes in the economic learning class XI IIS 4 SMA Negeri 7 Pontianak as evidenced by the increase in student motivation before the study 28%, the cycle I 57.14% And cycle II 74.28% at the time of the learning process. In addition, the increase in student learning outcomes that meet the KKM before the cycle of 32.28%, in the first cycle students who reached the KKM as much as 62.86% and the second cycle as much as 71.43%..Keywords: Cooperative Script & Motivation Learning Model and Learning Outcomes